Kemampuan dan Sikap Kader Kesehatan Melakukan Promosi Protokol Kesehatan dalam Melawan Pandemi COVID-19 - Merry Wijaya (STIKES Karya Husada Kediri, 2021)
Abstract COVID-19 pandemic poses great effects on healthcare system and huge potential of increasing the risk of public safety. Health protocol plays an important part in preventing the spread of COVID-19. However, many people do not fully understand the nature of such health protocol that COVID-19 pandemic is still a health problem priority in Indonesia. Health workers or cadres are chosen by the people and are trained to handle healthcare problems, both for individuals and for the public as a whole. They are expected to promote health protocol against COVID-19 in their service area. This study aims to discover health workers’ ability and attitude in promoting health protocol against COVID-19 among the public in their service area. This study employed quantitative research method, using cross-sectional design. Primary data was gathered through questionnaire, administered via google form to 126 active health workers who satisfied the inclusion criteria, which included having been serving for at least 6 consecutive months in Soreang Sub-district and being able to fill in google form questionnaire. The results of the study showed that most health workers’ knowledge about health protocol was in sufficient and good categories. However, there were some health workers who demonstrated negative attitude towards promoting health protocol against COVID-19. Their attitude was concluded negative because it did not satisfy the four aspects of health workers’ roles (motivation, communication, coordination, and mobilization) in performing their duties as integrated healthcare center workers. Keywords: Health Workers, Covid-19 Pandemic, Health Protocol Promotion.